PERBANDINGAN PRODUKSI PADI ORGANIK VARIETAS PANDAN WANGI DENGAN PUPUK CAIR ORGANIK DOSIS KELIPATAN 1,2,3 DAN 4 TAKAR PADA MUSIM TANAM 2011 - Karto k (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Organic  rice  is  the  rice  which  is  produced  from  the  organic  rice  development  activities  namely  the effort to develop rice using production input based on organic matters like animal waste, stacks, local organic  waste.  The  aim  of  this  research  is  to  investigate  the  comparison  among  the  organic  rice production “Pandan Wangi” through the use of liquid organic fertilizer on the dosage of 1, 2, 3 and 4 measurements  on  the  plantation  year  2011. The  method  used  on  this  experimental  research  was  the usage of POC especially when the plant grows on 15, 25 and 35 days with the dosage: (0 cc) for the control, 10 cc, 20 cc, 30 cc and 40 cc on each application. The data were analyzed by using chi square table.  The  research  shows  that  the  POC  dosage  on  the  organic  rice  variety  “Pandan  Wangi”  didn’t show any significant production differences. Keywords: POC, production, organic rice